2020
DOI: 10.1108/jhom-07-2019-0200
|View full text |Cite
|
Sign up to set email alerts
|

Innovation technology in neurorehabilitation: introducing a hub and spoke model to avoid patient “migration” in Sicily

Abstract: PurposeIn the Italian National Health Service, hospital planning has been influenced by two aspects: patients' freedom to choose their healthcare provider and the equal distribution of centers spread throughout country. Unfortunately, while every Italian region should be able to meet the health needs of its own inhabitants, consistent migration among regions exists, especially from the southern areas of the country, including Sicily. As it has been demonstrated that a hub-and-spoke model (HSM) can provide medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The biggest attractions were for MDC 8. The general picture of mobility was quite heterogeneous; southern regions had the greatest exports of patients and all showed negative mobility balances except for Molise, which has always had positive balances over the years [ 46 ], while the northern and central regions had the greatest attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest attractions were for MDC 8. The general picture of mobility was quite heterogeneous; southern regions had the greatest exports of patients and all showed negative mobility balances except for Molise, which has always had positive balances over the years [ 46 ], while the northern and central regions had the greatest attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Following this positive experience, the Italian Ministry of Health founded in 2015 a National Telerehabilitation network involving the main Research Institutes (i.e., the "Istituti di Ricovero e Cura a Carattere Scientifico, " IRCCS) and aimed at assessing the efficacy and cost-effectives analysis of telerehab in the treatment of different neurological disorders, including stroke, dementia, PD, and MS. Also, Calabrò et al (107) underlined the potential of telemedicine in guaranteeing distance training and comparison between the healthcare professionals, encouraging the relationship between the Hub center and the Spokes. In fact, these centers are constantly connected thanks to telemedicine: the different specialists support each other, both for diagnosis and for rehabilitation.…”
Section: Ongoing Projects and Future Perspectivesmentioning
confidence: 99%
“…In fact, these centers are constantly connected thanks to telemedicine: the different specialists support each other, both for diagnosis and for rehabilitation. Furthermore, this program allows the application of standard protocols with fairer and uniform health services (107).…”
Section: Ongoing Projects and Future Perspectivesmentioning
confidence: 99%
“…Various studies have shown that telerehabilitation could help supporting both physical and psychosocial needs of the individuals living at home with an improvement of motor, cognitive, or psychological disorders ( Bramanti et al, 2018 ; De Cola et al, 2016 ; Maggio et al, 2020 ; Zhou et al, 2020 ). Telerehabilitation is a field of telemedicine, consisting of systems/devices for the control of remote rehabilitation training, such as physiotherapy, speech therapy, occupational therapy, as well as assistance of patients forced to stay at home, without the physical presence of therapists or other healthcare professionals ( Calabrò et al, 2020 ; De Cola et al, 2020 ; Rosso et al, 2018 ). In particular, tele-cognitive rehabilitation involves the recovery and/or compensation of impaired cognitive and behavioral skills to improve the quality of life of the patient in his/her family and social environment.…”
Section: Introductionmentioning
confidence: 99%